The Role of m6A on Female Reproduction and Fertility: From Gonad Development to Ovarian Aging - Sun, Xiaoyan; Lu, Jiafeng; Li, Hong; Huang, Boxian (Frontiers in Cell and Developmental Biology, 2022)
The growth and maturation of oocyte is accompanied by the accumulation of abundant RNAs and posttranscriptional regulation. N6-methyladenosine (m6A) is the most prevalent epigenetic modification in mRNA, and precisely regulates the RNA metabolism as well as gene expression in diverse physiological processes. Recent studies showed that m6A modification and regulators were essential for the process of ovarian development and its aberrant manifestation could result in ovarian aging. Moreover, the specific deficiency of m6A regulators caused oocyte maturation disorder and female infertility with defective meiotic initiation, subsequently the oocyte failed to undergo germinal vesicle breakdown and consequently lost the ability to resume meiosis by disrupting spindle organization as well as chromosome alignment. Accumulating evidence showed that dysregulated m6A modification contributed to ovarian diseases including polycystic ovarian syndrome (PCOS), premature ovarian insufficiency (POI), ovarian aging and other ovarian function disorders. However, the complex and subtle mechanism of m6A modification involved in female reproduction and fertility is still unknown. In this review, we have summarized the current findings of the RNA m6A modification and its regulators in ovarian life cycle and female ovarian diseases. And we also discussed the role and potential clinical application of the RNA m6A modification in promoting oocyte maturation and delaying the reproduction aging.